Culture shock and difficulties of Korean students in Indonesia and the United States - Berthananditya Pahlevi Smaradwi Rani; Risa Triarisanti (Journal of Korean Applied Linguistics, 2022)
Overseas students will have difficulty adjusting to the norms and habits in the new environment. This impacts discomfort and unhappiness in adapting. This condition is termed culture shock. This study aims to determine the culture shock experienced by South Korean students and the difficulties in Indonesia and the United States. The data is collected by using a literature study with qualitative method. The result of this study shows that South Korean students in Indonesia and the United States experience culture shock and difficulties due to different cultures and languages with a percentage of 60-80%. The differences that arise between Korean students in Indonesia and the United States are the difficulties caused by transportation and services from students in Indonesia because they feel that transportation and services in Indonesia are still lacking and personal difficulties in the United States because of the individualism that makes most students in the US feel lonely and find it difficult to express. However, despite experiencing culture shock, this Korean student tried to adjust to the new culture with several efforts, such as doing private lessons with Indonesians, then hanging out and communicating with Indonesians, and trying to compromise with the culture and social rules around him so that he well received and as it is. Meanwhile, adaptation efforts in the United States include conducting orientation sessions and meetings with advisors and making teams when studying with students in various countries to help break down the natural tendency to get along with students from their nation.